RESIDUAL STRESS MEASUREMENTS AND STRUCTURAL INTEGRITY IMPLICATIONS FOR SELECTIVE LASER MELTED TI-6AL-4V - Knowles, CR; Becker, TH; Tait, RB (The South African Journal of Industrial Engineering, 2012)
Selective laser melting (SLM) of Ti-6Al-4V has significant potential in the aerospace and biotechnology industries. SLM employs a focused laser beam to melt successive layers of metallic powder into complex components. This process can result in the generation of high thermally-induced residual stresses. These residual stresses, together with micro-flaws/ pores from the inherent fabrication process, may lead to premature fatigue crack initiation and propagation at relatively low cyclic stresses. The hole-drilling strain gauge method was used to evaluate residual stresses within SLM Ti-6Al-4V specimens, with the intention of understanding the associated mechanisms for the successful application of SLM Ti-6Al-4V in industry.